Influenza A(H1N1)pdm09 Virus with Reduced Susceptibility to Baloxavir, Japan, 2024 - Takashita, Emi; Morita, Hiroko; Nagata, Shiho; Fujisaki, Seiichiro; Miura, Hideka; Ikeda, Tatsuya; Komabayashi, Kenichi; Sasaki, Mika; Matoba, Yohei; Takahashi, Tomoko; Ogawa, Naomi; Mizuta, Katsumi; et al. (Emerging infectious diseases, 2025)
Influenza A(H1N1)pdm09 virus carrying an I38N substitution was detected in an untreated teenager in Japan. The I38N mutant virus exhibited reduced susceptibility to baloxavir but remained susceptible to neuraminidase inhibitors and showed reduced growth capability. Monitoring antiviral drug susceptibility of influenza viruses is necessary to aid public health planning and clinical recommendations.